Solve the following system of equations using an inverse matrix. You must also indicate the inverse matrix, \( A^{-1} \), that was used to solve the system. You may optionally write the inverse matrix with a scalar coefficient. \[ \begin{array}{l}-2 x-4 y=1 \\ -6 x-9 y=-8\end{array} \] Answer Attempt sout of 2 \( A^{-1}= \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To solve the system of equations using an inverse matrix, first we need to convert the equations into matrix form, \( AX = B \). The system is given as: \[ \begin{array}{l} -2x - 4y = 1 \\ -6x - 9y = -8 \end{array} \] This can be expressed in matrix form as: \[ \begin{pmatrix} -2 & -4 \\ -6 & -9 \end{pmatrix} \begin{pmatrix} x \\ y \end{pmatrix} = \begin{pmatrix} 1 \\ -8 \end{pmatrix} \] Now, we define the matrices: \[ A = \begin{pmatrix} -2 & -4 \\ -6 & -9 \end{pmatrix}, \quad X = \begin{pmatrix} x \\ y \end{pmatrix}, \quad B = \begin{pmatrix} 1 \\ -8 \end{pmatrix} \] Next, we calculate the inverse of matrix \( A \) using the formula for the inverse of a 2x2 matrix: \[ A^{-1} = \frac{1}{det(A)} \begin{pmatrix} d & -b \\ -c & a \end{pmatrix} \] where \( A = \begin{pmatrix} a & b \\ c & d \end{pmatrix} \). Calculating the determinant: \[ det(A) = (-2)(-9) - (-4)(-6) = 18 - 24 = -6 \] Thus, the inverse \( A^{-1} \) is: \[ A^{-1} = \frac{1}{-6} \begin{pmatrix} -9 & 4 \\ 6 & -2 \end{pmatrix} = \begin{pmatrix} \frac{3}{2} & -\frac{2}{3} \\ -1 & \frac{1}{3} \end{pmatrix} \] Now, we use \( A^{-1} \) to find \( X \): \[ X = A^{-1}B = \begin{pmatrix} \frac{3}{2} & -\frac{2}{3} \\ -1 & \frac{1}{3} \end{pmatrix} \begin{pmatrix} 1 \\ -8 \end{pmatrix} \] Calculating the product: \[ X = \begin{pmatrix} \frac{3}{2} \times 1 + (-\frac{2}{3}) \times (-8) \\ -1 \times 1 + \frac{1}{3} \times (-8) \end{pmatrix} = \begin{pmatrix} \frac{3}{2} + \frac{16}{3} \\ -1 - \frac{8}{3} \end{pmatrix} \] Finding a common denominator for the first component: \(\frac{3}{2} = \frac{9}{6}\) and \(\frac{16}{3} = \frac{32}{6}\) \[ \text{First component: } \frac{9}{6} + \frac{32}{6} = \frac{41}{6} \] Finding the second component: \(-1 = -\frac{3}{3}\) \[ \text{Second component: } -\frac{3}{3} - \frac{8}{3} = -\frac{11}{3} \] So, the solution vector \( X \) is: \[ X = \begin{pmatrix} \frac{41}{6} \\ -\frac{11}{3} \end{pmatrix} \] Thus, the final answer is: \[ A^{-1} = \begin{pmatrix} \frac{3}{2} & -\frac{2}{3} \\ -1 & \frac{1}{3} \end{pmatrix} \]